Appians Κελτική Einleitung, Text, Übersetzung und Kommentar - Hofeneder, Andreas (Holzhausen, 2018)
Appian's Celtic History, which deals with the military conflicts between Romans and Celts from the 4th cent. BC until the conquest of Gaul by Caesar, is despite its fragmentary state a valuable source, as it contains various information documented nowhere else or significantly different to those traditions attested by other authors. In addition to the Greek text and a German translation of the individual fragments, the present publication offers above all the first detailed commentary, which makes this little regarded source accessible.